Prediction of Ovarian Response by Antimullerian Hormone in Women with Polycystic Ovarian Syndrome: A Randomized Prospective Study - Elsaid N (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2016)
Objective: To assess the effect of high level of circulating antimullerian hormone on the outcome of gonadotrophin ovulation induction in women with polycystic ovarian syndrome.  Patients and Methods: This was a prospective study performed at Ain Shams University Maternity Hospital, over a 3-year period, between Jan 2013 and Jan 2016, and included 300 women who were presented at the infertility clinic and scheduled for having gonadotrophin ovulation induction. Participant ages ranged from 18 to 35 years, the patients were divided into two equal groups; group I (N=150) included women with PCOS having antimullerian hormone < 7.7 mg/dl and group II (N=150) which included women with PCOS with antimullerian hormone ≥ 7.7 mg/dl. The two groups underwent gonadotrophin stimulation of the ovary, serum AMH concentrations were measured on cycle day 3 before the commencement of gonadotrophins ovarian induction. Ovarian response and the biochemical and clinical pregnancy rates were analyzed in both groups.  Results: The outcomes of 300 cycles were analyzed, the ovarian response and biochemical and clinical pregnancy rates were higher in group I women who ovulated after therapy compared with the group II. There was a statistically significant gradient rise of serum AMH levels with the increasing dose of gonadotrophins required to achieve ovulation (P<0.05). AMH was an independent predictor of ovulation induction by gonadotrophins in PCOS women. AMH was demonstrated to be a useful predictor of gonadotrophins ovulation induction in PCOS women, having 92 % specificity and 65 % sensitivity when the threshold AMH concentration was 7.7 ng/ml.  Conclusions: Serum AMH might be clinically helpful to predict which PCOS women are more likely to respond to gonadotrophin therapy and eventually to direct the selection of protocols of ovulation stimulation.